Balancing cardiovascular (CV) and cancer death among patients with small renal masses: modification by CV risk. (27th July 2014) - Patel, Hiten D.; Kates, Max; Pierorazio, Phillip M.; Allaf, Mohamad E.
<x xml:space="preserve">Abstract</x> Objective To assess modification of comparative cancer survival by cardiovascular (CV) risk and treatment strategy among older patients with small renal masses (SRMs). Patients and Methods Patients with localised T1a renal cell carcinoma were identified in the Surveillance, Epidemiology and End Results‐Medicare database (1995–2007). Patients were stratified by CV risk, using major atherosclerotic CV comorbidities identified by the Framingham Heart Study, to compare overall (OS), cancer‐specific (CSS), and CV‐specific survival (CVSS) for those who deferred therapy (DT) to those undergoing either partial (PN) or radical nephrectomy (RN). Cox proportional hazards and Fine and Gray competing risks regression adjusted for demographics, comorbidities, and tumour size were performed. Results In all, 754 (10.5%) patients had DT, 1849 (25.8%) patients underwent PN, and 4574 (63.7%) patients underwent RN. Patients at high CV risk who had DT had the greatest CV‐to‐cancer mortality rate ratio (2.89), and CV risk was generally associated with worse OS and CVSS. Patients in the high CV risk strata had no difference in CSS between treatment strategies [DT vs PN: hazard ratio (HR) 0.59, 95% confidence interval (CI) 0.25–1.41; DT vs RN: HR 0.81, 95%CI 0.46–1.43)], while there was a 2–4 fold CSS benefit for surgery in the low CV risk strata. Conclusions Cancer survival was comparable across treatment strategies for older patients with SRMs with high risk CV disease. Greater attention to CV comorbidity as it relates to competing risks of death and life expectancy may be deserved in selecting patients appropriate for active surveillance because patients at low CV risk might benefit from surgery.